Reference intervals for stool calprotectin in preterm neonates and their utility for the diagnosis of necrotizing enterocolitis. (October 2018) - MacQueen, B.; Christensen, R.; Yost, C.; Gordon, P.; Baer, V.; Schlaberg, R.; Lowe, J.
Abstract Objective Calprotectin is an antimicrobial protein found in stool when released by granulocytes. We sought to create stool calprotectin reference ranges in preterm neonates and to evaluate whether levels exceeding the upper reference interval are diagnostic for necrotizing enterocolitis (NEC). Study design Stool calprotectin was measured in premature neonates without gastrointestinal pathology to create reference intervals. For comparison, levels from infants undergoing "rule out NEC" evaluations were plotted on these reference intervals. Results Stool calprotectin reference intervals were created according to gestational age at birth and corrected gestational age. Levels during "rule out NEC" evaluations were more often above the upper reference interval with NEC vs. those without NEC. Conclusions Stools from preterm neonates have a higher range of calprotectin than stools from healthy term neonates. In evaluating preterm neonates for NEC with stool calprotectin, a calprotectin upper reference interval that incorporates corrected gestational age best predicts the diagnosis of NEC.